Optimizing ECAP recording parameters in pediatric cochlear implantation: a clinical perspective - Nandan, Maruti; Sinha, Richi; Sharma, Amit Kumar; Kumar, Amit; Singh, Rohit Raj; Singh, Rakesh Kumar (International Journal of Research in Medical Sciences, 2025)
Background: Intraoperative ECAP (electrically evoked compound action potential) monitoring provides critical objective data during pediatric cochlear implantation, where behavioral feedback is often unavailable. Despite its clinical importance, there is considerable variability in ECAP recording protocols, leading to inconsistent waveform quality and limited inter-institutional reproducibility. This study aimed to identify and validate optimal ECAP recording parameters that enhance signal fidelity and suppress artifacts, thereby improving intraoperative assessment and programming consistency. Methods: Fifty-six pediatric patients undergoing cochlear implantation with Cochlear Nucleus devices were prospectively included. ECAPs were recorded using AutoNRT software while systematically varying four parameters: pulse width (25, 37, 50 μs/phase), stimulation rate (50, 80, 120 Hz), recording electrode separation (0, 1, 2, 3 contacts) and recording delay (0.2, 0.4, 0.6 ms). Recordings were assessed for waveform clarity, N1 latency, peak-to-peak amplitude, signal-to-noise ratio and residual artifact. Results: The combination of 25 μs/phase pulse width, 80 Hz stimulation rate, 1–2 electrode separation and 0.4 ms recording delay produced the most reliable ECAP waveforms. These settings resulted in clearly defined N1-P2 peaks, higher amplitude consistency across the electrode array, superior signal-to-noise ratios and effective artifact suppression compared to other configurations. Conclusions: The adoption of standardized ECAP recording settings significantly enhances intraoperative telemetry quality in pediatric CI recipients. These parameters facilitate more accurate assessment of neural responses, support consistent device programming and may ultimately contribute to improved auditory outcomes.